2002
DOI: 10.1039/b200625c
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study on the stability and spectra of cycloaddition products: Methylene-β-lactam isomers

Abstract: The theoretical thermodynamic stability was calculated for products of cycloaddition of vinylimine to ketene and isocyanic acid to allene by using the MP2, DFT(B3PW91), and HF methods involving the 6-311++G** basis set. These cycloaddition reactions could yield fourteen different molecules; practically however, free Gibbs energies calculated for the considered molecules suggest that only 4-and 3-methylene-b-lactams can be formed in observable amounts. For these particular isomers the heats of formation, geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…25 We demonstrated that out of the 11 possible products of such a reaction, 4-methyleneβ-lactam is the one most stable thermodynamically. 25 However, no other theoretical nor experimental paper has dealt with this reaction. On the other hand, we did not consider the mechanism of this reaction, and this seems to be desirable as the experimental findings report 2-iminooxetanes to be the main product of the catalyzed cycloaddition reaction of vinylimine with ketenes or aldehydes.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…25 We demonstrated that out of the 11 possible products of such a reaction, 4-methyleneβ-lactam is the one most stable thermodynamically. 25 However, no other theoretical nor experimental paper has dealt with this reaction. On the other hand, we did not consider the mechanism of this reaction, and this seems to be desirable as the experimental findings report 2-iminooxetanes to be the main product of the catalyzed cycloaddition reaction of vinylimine with ketenes or aldehydes.…”
Section: Introductionmentioning
confidence: 92%
“…Also, the ketene−vinylimine cycloaddition reaction could possibly yield 4-methylene-β-lactams . We demonstrated that out of the 11 possible products of such a reaction, 4-methylene-β-lactam is the one most stable thermodynamically . However, no other theoretical nor experimental paper has dealt with this reaction.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations